Development and Educational Impact of a Low-Cost 3D-Printed Amniocentesis Simulator for Obstetrics and Gynaecology Resident Training: A Prospective Interventional Study - J, Dr Manaswini; A, Dr Parimala (International Journal of Aquatic Research and Environmental Studies, 2026)
Background: Amniocentesis is a technically demanding ultrasound-guided invasive procedure that requires precision and experience to minimize complications. Opportunities for hands-on training are limited because of ethical concerns and patient safety. Simulation-based education offers a safe alternative for skill acquisition. We developed a low-cost, reusable 3D-printed amniocentesis simulator and evaluated its impact on procedural performance among postgraduate trainees. Methods: A prospective pre–post interventional study was conducted among ten obstetrics and gynecology postgraduate residents. Participants were assessed using a structured seven-step performance checklist before simulator training and again after structured practice on the 3D-printed model. Total performance scores were compared using paired t-test. Effect size and 95% confidence intervals were calculated. Results: Mean performance score increased from 26.6 ± 2.32 before training to 56.1 ± 2.02 after training. The mean improvement was 29.5 ± 2.76 points. Paired t-test showed a highly significant difference (t(9)=33.8, p<0.0001). The 95% CI for improvement was 27.5–31.5. Effect size was extremely large (Cohen’s d=10.7). Conclusion: The 3D-printed simulator produced substantial improvement in technical competence and represents an affordable, scalable solution for procedural training in fetal medicine programs.